The basics of Edmund D. Pellegrino’s medical ethics - Żołnierz, Joanna; Sak, Jarosław (Journal of Education, Health and Sport, 2018)
Introduction: Edmund D. Pellegrino, one of the leading representatives of virtue ethics in medicine, after a deep analysis of different concepts of medical ethics and bioethics, with their weaknesses and limitations, proposes the return to Aristotelian teleology. In his numerous works devoted to the philosophy of medicine, he makes comprehensively developed and well-presented assumptions and postulates on ethics in medical practice. Strongly embedded in the concept of human nature, referring to the Hippocratic heritage, Thomism and Christian values, theory of ethics is an extremely interesting proposition and seems well suited to the challenges of modern medicine. Objective: The aim of the article is to present a general outline of philosophical assumptions underlying Edmund D. Pellegrino’s medical ethics concept. This outstanding philosopher of medicine, whose contribution to the development of this scientific field is impressive, focuses mainly on a detailed description and indication of sources of medicine and doctor’s moral duties. Conclusions: The work will briefly present fundamental issues for his concept of medical ethics: the nature of medicine and the nature of the doctor–patient relationship, as well as the concept of a good/virtuous? person. Additionally, factors shaping the relationship between a doctor and a sick person, such as the act of medicine, the act of profession and the fact of illness, will also be covered. These factors play a significant role in understanding the nature of the doctor–patient relationship and allow to accurately determine the telos of medicine.